Histological changes in cervical lymph nodes following clinical irradiation. - Burge, J. S. (1975)
Clinical radiation in man is shown to have similar effects to single dose irradiation in animals. While it is not possible by examining individual nodes to estimate the dose of radiation they have received, progressive changes with increasing doses can be seen leading to loss of lymphoid tissue and replacement by fibrous tissue. Functional changes probably occur, leading to loss of the filtering power of the nodes and their by-pass by anatomotic lymph channels. The purpose of this paper is in no way an appeal to discard radiation as a form of treatment for cancer. The destructive effects of radiation have been known form some time, but the significance of the regional nodes in the immune response to tumour has only recently been considered. A reappraisal is required of the way radiation therapy is given, so that as much as possbile of the immune mechanism may be left undamaged.